4D printing system stimulated by curcumin/whey protein isolate nanoparticles: A comparative study of sensitive color change and post-processing. (April 2023) - Shen, Chen; Chen, Wenqing; Li, Changzhu; Chen, Xiaochen; Cui, Haiying; Lin, Lin
Abstract: In order to provide a more reliable curcumin stabilization scheme and efficient post-treatment process in food 4D printing system, this study innovatively introduced nano-embedding technology and catalytic infrared drying (CID) method to develop interesting color-changing materials for 4D printing based on thermal response stimuli. Firstly, curcumin (C) was encapsulated into whey protein isolate (WPI) to form nanoparticles (C-WPI-NPs), which were further added to potato starch-xanthan gum base to fabricate printing ink. The effects of C-WPI-NPs addition on the rheological properties, moisture distribution, and FTIR spectra of printing ink were investigated. It was demonstrated that the addition of C-WPI-NPs increase water-holding capacity and viscosity of the printing ink, and formation of a dense gel network while reducing water molecule movement. This resulted in excellent elastic solid-like behavior and mechanical strength against compression deformation of the printing ink. Subsequently, the effects of three drying post-treatment methods were compared, including catalytic infrared drying (CID), microwave drying (MD) and hot air drying (HAD). Compared with MD and HAD, CID showed a more uniform color change. The retention rate of curcumin under CID treatment reached 62.17%, which avoiding significant degradation of nutrients. Moreover, CID also showed great advantages in antioxidant capacity. The scavenging rate of DPPH radical was 52.69%, which was much higher than that of HAD (38.99%) and MD (36.04%). In addition, the appearance of the printed product was better preserved, and the dimensional offset rate was only 7.64%. Highlights: Curcumin/whey protein isolate nanoparticles (C-WPI-NPs) are fabricated successfully. The 3D printing ink show preferable printability after addition of C-WPI-NPs. The color change is achieved by heating the 3D printing product with C-WPI-NPs. Catalytic infrared drying (CID) technology exhibit excellent post-treatment effects.